Musca domestica Cecropin (Mdc) Alleviates Salmonella typhimurium-Induced Colonic Mucosal Barrier Impairment: Associating With Inflammatory and Oxidative Stress Response, Tight Junction as Well as Intestinal Flora - Zhang, Lun; Gui, Shuiqing; Liang, Zhaobo; Liu, Along; Chen, Zhaoxia; Tang, Yanan; Xiao, Mingzhu; Chu, Fujiang; Liu, Wenbin; Jin, Xiaobao; Zhu, Jiayong; Lu, Xuemei (Frontiers in Microbiology, 2019)
Salmonella typhimurium (S. typhimurium), a Gram-negative food-borne pathogen, induces impairment in intestinal mucosal barrier function frequently. The injury is related to many factors such as inflammation, oxidative stress, tight junctions and flora changes in the host intestine. Musca domestica cecropin (Mdc), a novel antimicrobial peptide containing 40 amino acids, has potential antibacterial, anti-inflammatory and immunological functions. It remains unclear exactly whether and how Mdc reduces colonic mucosal barrier damage caused by S. typhimurium. Twenty four 6-week-old male mice were divided into four groups: normal group, control group (S. typhimurium-challenged), Mdc group and ceftriaxone sodium group (Cs group). HE staining and Transmission electron microscopy (TEM) were performed to observe the morphology of the colon tissues. Bacterial load of S. typhimurium in colon, liver and spleen were determined by bacterial plate counting. Inflammatory factors were detected by enzyme linked immunosorbent assay (ELISA). Oxidative stress levels in the colon tissues were also analyzed. Immunofluorescence analysis, RT-PCR and Western blot were carried out to examine the levels of tight junction and inflammatory proteins. The intestinal microbiota composition was assessed via 16s rDNA sequencing. We successfully built and evaluated an S. typhimurium-infection model in mice. Morphology and microcosmic change of the colon tissues confirmed the protective qualities of Mdc. Mdc could inhibit colonic inflammation and oxidative stress. Tight junctions were improved significantly after Mdc administration. Interestingly, Mdc ameliorated intestinal flora imbalance, which may be related to the improvement of tight junction. Our results shed a new light on protective effects and mechanism of the antimicrobial peptide Mdc on colonic mucosal barrier damage caused by S. typhimurium infection. Mdc is expected to be an important candidate for S. typhimurium infection treatment.